Knowledge and Skills of Change Agents in Rural Community Development in Sukabumi Regency Indonesia - Ocktilia, Helly (International Journal of Psychosocial Rehabilitation, 2020)
The study was motivated by the importance of an agent of change presence in the success of community development. The study aimed to obtain an in-depth overview of the Change Agents competencies in the implementation of community development programs. The aspects of competencies studied are knowledge and skills possessed by Change Agents. The study was conducted in rural areas of Sukabumi Regency Indonesia which became the implementation area of Desa Sejahtera Mandiri (independent prosperous village) model from the Ministry of Social Affairs of the Republic of Indonesia. The study uses descriptive methods with a qualitative approach. The informants consisted of District Social Welfare Workers (TKSK), Community Leaders, and Community Cadres. The results shows that the aspects of knowledge possessed by agents of change are patterns of social interaction that must be developed by both the community, develop empathy for the problems and needs of the community, plays roles following social environment, resources that can be used to address community problems and needs, and develop attitudes that are appropriate to the culture of the community. The skills aspect shows that change agents have skills such as personal communication, facilitating groups, motivating, increasing enthusiasm and activating the community, providing resources for the community, overcoming conflicts and conducting negotiations and mediations.